PENGARUH LINGKUNGAN TEMAN SEBAYA TERHADAP PERILAKU KONSUMTIF MELALUI KONTROL DIRI SISWA DI SMA YLPI PEKANBARU - Fitriani Fitriani (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
This research aims to know: 1) The effect of peer environment on consumer behavior the student in SMA YLPI Pekanbaru, 2 ) the effect of peer environment on self control the student in SMA YLPI Pekanbaru, 3) the effect of self control on consumer behavior the student in SMA YLPI Pekanbaru, 4) the effect of peer environment on consumer behavior thourgh self control student in SMA YLPI Pekanbaru. This type of research is quantitative research with the population is class XI academic year of 2018/2019 with a total of 98 students, and all of them are used as research samples. Data collection techniques used the likert scale questionnaires. Questionnaire used to reveal data about the peer environment, self control, and consumer behavior the student. The data were analyzed using a descriptive statistical analysis, classical assumption test, sobel test and path analysis. The results of this study show: 1) peer environment has a positive effect on consumer behavior as big as 0,253, 2) peer environment has a positive effect on self control as big as 0,209, 3) self control has a negative effect on consumer behavior as big as -0,284. 4) Self-control mediate between the peer environment to consumer behavior.